Strategi Pengembangan Daya Tarik Wisata Pasar Buah Berastagi Bagi Wisatawan - Irma Yusriani Siamora; Nurdini Lady Taminta Br. Purba; Ika Sartika; M. Alpa Rizky (Lembaga Pengembangan Kinerja Dosen, 2024)
Karo is a district in the province of North Sumatra, Indonesia. The capital of this district is located in Kabanjahe sub-district. Karo Regency is located on the Karo plateau, in the Bukit Barisan mountains. The purpose of writing this journal is to find out the strategies used to develop the attractiveness of the Berastagi fruit market for tourists. The research method in this journal is quantitative research. The quantitative research used is survey research. This research collects data obtained from the Karo community. The result of this research is that the government is participating in developing the attraction for tourist attractions in Berastagi, namely the fruit market.